(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Performance is not only seen in terms of effectiveness and efficiency, but also related to the mental attitude of employees who always want continuous improvement. This study aims to determine the influence of emotional intelligence, work ethic and human relations on employee performance. The questionnaire was tested with validity and reliability tests given to 40 respondents. The collected data is analyzed using multiple linear regression analysis, determination, F-test and t-test. From the analysis obtained (1) Emotional intelligence has a positive and significant effect on the performance of employees at PT. BPR Tish Batubulan Gianyar, (2) Work ethic has a positive and significant effect on employee performance at PT. BPR Tish Batubulan Gianyar, (3) Human relation has a positive and significant impact on employee performance at PT. BPR Tish Batubulan Gianyar, and (4) Emotional intelligence, work ethic and human relations simultaneously have a positive and significant effect on the performance of employees at PT. BPR Tish Batubulan Gianyar.